2006
DOI: 10.1055/s-2006-944732
|View full text |Cite
|
Sign up to set email alerts
|

High-magnification chromoscopic colonoscopy in ulcerative colitis: a valid tool for in vivo optical biopsy and assessment of disease extent

Abstract: This is the largest prospective study and the only Western group to report on this application of magnification imaging. High-magnification imaging provides a sensitive and specific in vivo "virtual biopsy" in ulcerative colitis and so an instant biomarker for disease relapse, while accurately predicting disease extent. High-accuracy optical biopsy can limit the number of biopsies required, with significant cost savings for pathology services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 10 publications
1
37
0
3
Order By: Relevance
“…Hence, target biopsies of suspicious lesions might provide more effective surveillance than taking random biopsies. [28][29][30] Hurlstone et al 31,32 reported on the efficacy of magnifying colonoscopy in UC using ''optical biopsy'' for the surveillance of colitic cancer and disease extent. Nishizawa et al 33 first reported the healing process patterns of UC mucosa using the feature of magnifying colonoscopy.…”
Section: Histological Findingsmentioning
confidence: 99%
“…Hence, target biopsies of suspicious lesions might provide more effective surveillance than taking random biopsies. [28][29][30] Hurlstone et al 31,32 reported on the efficacy of magnifying colonoscopy in UC using ''optical biopsy'' for the surveillance of colitic cancer and disease extent. Nishizawa et al 33 first reported the healing process patterns of UC mucosa using the feature of magnifying colonoscopy.…”
Section: Histological Findingsmentioning
confidence: 99%
“…Mucosal lesions can be characterized by the Pit Pattern Classification [10] . The largest prospective study compared conventional endoscopy with magnification endoscopy in 300 patients with UC and found a high correlation of magnification with disease activity and histopathological grading [11] . It seems to be of high diagnostic relevance to combine chromoendoscopy with magnification.…”
Section: Magnification Endoscopymentioning
confidence: 99%
“…A laborious protocol has been proposed involving not only target biopsies from suspicious lesions, but also two to four random biopsies taken every 10 cm of the colon [32] . MCC has emerged as the best method currently available for identifying dysplastic lesions in an inflammatory bowel disease setting [33,34] . In ter ms of NBI research, the limitations of the first NBI prototype were recently shown in a prospective randomized crossover study of 42 patients with longstanding ulcerative colitis.…”
Section: Detection Of Dysplastic Areas In Ulcerative Colitismentioning
confidence: 99%